(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
Study seeks to give an idea of ​​Zakat as one of the important pillars of Islam as a cult of the hand and the Hereafter and of being a means of growth and economic development on the other. It is not a tax subsidy, but the status of a positive target: the redistribution of income imposed on the rich to help the poor class and the poor, and injected into the cycle of income, and contribute to the increase in consumption, production, and employment.